Individual differences in loss aversion: conscientiousness predicts how life satisfaction responds to losses versus gains in income - Boyce, Christopher J.; Wood, Alex M.; Ferguson, Eamonn (SAGE, 2016)
Loss aversion is considered a general pervasive bias occurring regardless of context or person making the decision. We hypothesized that conscientiousness would predict an aversion to losses in the financial domain. We index loss aversion by the relative impact of income losses and gains on life satisfaction. In a representative German sample (N¬ = 105,558: replicated in a British sample, N = 33,848), with conscientiousness measured at baseline, those high on conscientiousness have the strongest reactions to income losses, suggesting a pronounced loss aversion effect, whilst for those moderately un-conscientious there is no loss aversion effect. Our research; (a) provides the first evidence of personality moderation of any loss aversion phenomena; (b) supports contextual perspectives that both personality and situational factors need to be examined in combination; (c) shows that the small but robust relationship with life satisfaction is primarily driven by a subset of people experiencing highly impactful losses.